Komunikasi Dakwah dalam Transformasi Sosial: Analisis Sosiologis Metode Komunikasi Syekh Yusuf Al-Makassari dan Adaptasinya di Era Digital - Ijjas (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This study analyses the communication patterns of Sheikh Yusuf al-Makassari (1626-1699) from a sociological perspective and their relevance to the transformation of contemporary communication. Using qualitative methods with an interpretive sociological approach, this study examines how Sheikh Yusuf's communication strategies in a pluralistic society succeeded in creating social change. The findings show that Sheikh Yusuf used three communication models: (1) adaptive-contextual communication through a hikmah approach, (2) persuasive-empathetic communication through mau'idzah hasanah, and (3) dialogical-participatory communication through mujadalah. This study found that Sheikh Yusuf's da'wah communication patterns underwent a transformation in the digital era, but still maintained the basic principles of humanistic and non-coercive communication. The contribution of this study is identifying effective da'wah communication models in pluralistic societies as an alternative to extreme da'wah communication on social media.